Study of Poisoning Cases in an Indian Tertiary Care Teaching Hospital - Panda, Bibhuti Bhusana; Hansda, Manoj Kumar; Mishra, Kunal; Samantsinghar, Pusparaj (Journal of Indian Academy of Forensic Medicine, 2015)
Morbidity and mortality as a result of poisoning, is a raging problem worldwide. The poignant part of the problem is that these are mostly preventable, if a basic treatment infrastructure facility is available with immediate accessibility. The present study was conducted from August 2013 to January 2014 in IMS & SUM Hospital, a tertiary care teaching hospital at Bhubaneswar, Odisha, India. In this prospective study we analyze, the various factors that play a role in the poisoning cases and the treatment outcome along with attempts to find solutions to prevent such tragic deaths and morbidity, in this part of the country. In this study incidence of poisoning cases are 40% out of all medico-legal cases registered. Most of the poisoning cases are males, aged between 20 to 30 years and unmarried. Suicide is the most common manner of poisoning. Home is the most suitable site for poisoning, followed by work place and remote place. Insecticides are the most common poison encountered in this region, followed by snake bite. Majority of the patients presented to the hospital within four hours of poisoning and most of them were completely cured after the treatment.